Influence of adhesive interface properties on the post-buckling response of composite I-stiffened panels with lateral support under axial compression. Issue 12 (18th June 2021) - Zhou, Rui; Gao, Weicheng
Abstract: The post-buckling carrying capacity is a major concern in the engineering design of composite stiffened panels, and is obviously influenced by the properties of the skin-stiffener adhesive interface. This work investigated the influence of adhesive interface properties on the post-buckling response of composite I-stiffened panels with lateral rib support under axial compression. After the compression tests, the buckling instability, post-buckling carrying capacity and failure mode of the specimens were obtained. The post-buckling process and failure mechanism of the stiffened panels were then analyzed in detail through finite-element (FE) method. With the validated FE model, the post-buckling response of composite stiffened panels with different interface adhesive materials combined with different bonding methods were simulated and compared. A further parametric analysis was implemented in analyzing the influence of skin-stiffener interface strength and critical strain energy release rate on the post-buckling responses of composite stiffened panels. The results indicate that the property of interface strength affects the post-buckling carrying capacity within a certain limit, and the critical interface strength is achieved. The properties of both interface strength and interface critical strain energy release rate have effects on the structural failure process and failure mode.